2011
DOI: 10.4236/jbnb.2011.23039
|View full text |Cite
|
Sign up to set email alerts
|

Bone Remodeling, Biomaterials And Technological Applications: Revisiting Basic Concepts

Abstract: Presently, several different graft materials are employed in regenerative or corrective bone surgery. However current misconceptions about these biomaterials, their use and risks may compromise their correct application and development. To unveil these misconceptions, this work briefly reviewed concepts about bone remodeling, grafts classification and manufacturing processes, with a special focus on calcium phosphate materials as an example of a current employed biomaterial. Thus a search on the last decade wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The proliferation of bone cells is responsible for tissue regeneration, and osteocyte survival in the grafted areas depends directly on the blood supply and on the vitality of the periosteum [24].…”
Section: Resultsmentioning
confidence: 99%
“…The proliferation of bone cells is responsible for tissue regeneration, and osteocyte survival in the grafted areas depends directly on the blood supply and on the vitality of the periosteum [24].…”
Section: Resultsmentioning
confidence: 99%
“…The long-term degradation (3–6 months) of the pericardium-based collagen membrane, when used in combination with a titanium mesh, can provide a sufficient barrier function in periorbital cleft coverage, thereby supporting periosteal tissue creeping and defect closing [26]. At a six-month post-operative checkup, it is shown that eye movements were significantly improved by using a collagen barrier membrane in combination with titanium mesh for orbital floor reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the collagen might not function purely as a barrier material, but also as an extracellular matrix, supporting the periosteal tissue. The periosteum, which is a soft tissue layer of bone tissue, consisting of the Stratum fibrosum and the Stratum osteogenicum , are already physiologically composed of collagen [26]. Furthermore, collagen-based biomaterials have been used for successful regeneration and repair of ligament tissue [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The future of biosynthetic bone implants will point to better mimicking the autologous bone grafts. Therefore, the composition, structure and molecular surface chemistry of various types of CaPO 4 will be tailored to match the specific biological and metabolic requirements of tissues or disease states [943,944]. This new generation of CaPO 4 bioceramics should enhance the quality of life of millions of people, as they grow older.…”
Section: Discussionmentioning
confidence: 99%